Ao Sul das Cortes: a Independência na Província do Rio Grande de São Pedro do Sul - Marcia Eckert Miranda (Centre de Recherches sur les Mondes Américains, 2013)
The Province of Rio Grande de São Pedro do Sul was the southernmost one of Brazil, where the dispute between the iberian crowns generated a military society. In the Joanine period, the invasion and the incorporation of the Banda Oriental was a factor of co-optation of military ranchers from that province into Court projects in Rio de Janeiro. In this article, the Independence process in the Província de São Pedro is analyzed, taking into consideration the military character of this society, the importance of militias, the cleavages and debates as to the distinct political projects and the consolidation of the province's economical and political elites's interests in the paths of the old platin colonies.